Populisme, Politik Pertahanan, Dan Pemimpin Lokal - Haboddin, Muhtar (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2019)
Populism, defence politics, and local leader are interrelated in the study of power. In the framework of maintaining power, local leaders will use populist policies to gain political support from the community. Community support is essential in an electoral democracy. Therefore, the local leaders will respond to the needs of its citizens in the form of populist policy. The ability of local leaders to meet the needs of their citizens is an important part of the working of populist politics. In this populist politics, the beneficiaries are leaders and society. Nevertheless, the beneficiaries are more certainly the local leaders. Why? Is it because local leaders use populism policies as instrumentation in maintaining power? By relying on that question, the choice of populist policy is aimed at two things for the local leaders. First, to gain legitimacy from the community. For local leaders, legitimacy is needed in building political power (Ramlan Surbakti, 1992; 96). It’s because the strong legitimacy will make to the local leaders more confident. Second, to strengthen the personal capacity of the local leaders in front of the community and other political forces. By relying on these two goals, the local leaders will have power stronger. Strengthening and maintaining power are the main objective for the local leaders. Therefore, this paper will attempt to present the ability of the local leaders in maintaining his power through the politics of populism at the local level (Vedi R Hadiz, 2017; Willy Purna Samadhi, 2016).